Effects of lowering LDL cholesterol on progression of kidney disease. - Haynes, R; Lewis, D; Emberson, J; Reith, C; Agodoa, L; Cass, A; Craig, J; de Zeeuw, D; Feldt-Rasmussen, B; Fellström, B; Levin, A; Wheeler, D; et al. (2014)
Lowering LDL cholesterol reduces the risk of developing atherosclerotic events in CKD, but the effects of such treatment on progression of kidney disease remain uncertain. Here, 6245 participants with CKD (not on dialysis) were randomly assigned to simvastatin (20 mg) plus ezetimibe (10 mg) daily or matching placebo. The main prespecified renal outcome was ESRD (defined as the initiation of maintenance dialysis or kidney transplantation). During 4.8 years of follow-up, allocation to simvastatin plus ezetimibe resulted in an average LDL cholesterol difference (SEM) of 0.96 (0.02) mmol/L compared with placebo. There was a nonsignificant 3% reduction in the incidence of ESRD (1057 [33.9%] cases with simvastatin plus ezetimibe versus 1084 [34.6%] cases with placebo; rate ratio, 0.97; 95% confidence interval [95% CI], 0.89 to 1.05; P=0.41). Similarly, allocation to simvastatin plus ezetimibe had no significant effect on the prespecified tertiary outcomes of ESRD or death (1477 [47.4%] events with treatment versus 1513 [48.3%] events with placebo; rate ratio, 0.97; 95% CI, 0.90 to 1.04; P=0.34) or ESRD or doubling of baseline creatinine (1189 [38.2%] events with treatment versus 1257 [40.2%] events with placebo; rate ratio, 0.93; 95% CI, 0.86 to 1.01; P=0.09). Exploratory analyses also showed no significant effect on the rate of change in eGFR. Lowering LDL cholesterol by 1 mmol/L did not slow kidney disease progression within 5 years in a wide range of patients with CKD.